Evaluasi Implementasi Sistem Manajemen Keselamatan Konstruksi (SMKK) Pada Proyek Waron Hospital - Prasetyo, Fahrudin Sugih; Harsono, Budwi (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2025)
Facilities in Surabaya have been developing rapidly in line with the increasing construction of urban infrastructure. Various infrastructure projects are being carried out to enhance the quality of urban facilities and attract investors. One of the most prominent aspects of development is the growing number of high-rise building constructions in Surabaya. In every construction project, the implementation of Occupational Safety and Health (OSH) is a crucial factor that must be considered. OSH serves as a guideline that reminds workers of the importance of maintaining their health, safety, and security while working. This study aims to analyze the implementation of the OSH work program in the Waron Hospital construction project. Data was collected through questionnaires and direct interviews, then analyzed using descriptive statistics with standard deviation and mean methods. Based on the data collected, 48 respondents were directly involved in the project. The study results indicate that the implementation of the OSH program in this project still faces various challenges. Some contributing factors include the company's limited OSH budget, the relatively small project contract value, and the low awareness among workers regarding the importance of the OSH program for their safety.